Modeling of anomaly detection for cyber security of the substation - Lin, Dong. (2013)
As the continuous increase of environment issues and energy demand for recent decades, the deeper development of smart power grid has already become a significant research topic all over the world. In order to cope with the challenges, innovative research from many other different disciplines, such as security, complex systems engineering, social